Sovražnost in nasilje v digitalni kulturi ter dobi umetne inteligence - Centa Strahovnik, Mateja (Bogoslovni vestnik, 2025)
The article discusses the forms, characteristics and specificities of online hate, hostility and violence in the digital culture. At the same time, it highlights some of the forms that are specific to artificial intelligence, or that are significantly transformed by the use of AI technologies. The paper also deals with the fundamental characteristics of such hatred and violence, highlighting in particular those that concern the emotional or affective domain. The article discusses compassion as one of the subdomains for overcoming online hate and violence. In conclusion, the article addresses the question of an adequate or holistic understanding of compassion and its role in digital culture, including the aspects highlighted by theology. Compassion is not only a morally central and private emotion, but a socially and politically important attitude that needs to be cultivated in the digital culture in order to support the development of a just society, the full respect for human dignity and the proper functioning of democratic institutions.
Keywords: artificial intelligence; digital culture; digitalna kultura; hostility; nasilje; online hate; sovražnost; spletno sovraštvo; umetna inteligenca; violence